The legislated return of the golden age in the Aeneid through agriculture and peace. Redeunt Saturnia Regna (Argos, 2022)
Vergil elaborated the golden age myth in his works and he conceived it as possible at his present time. The aim of our paper is to analyze the mentions in the Aeneid of the golden age Italian rulers, Saturn and August, as a mythical and historical continuum. We set out to demonstrate that the golden return in the Aeneid, according to his previous works (Ecl. and G.), can only take place if there is a good ruler, who achieves specific conditions, as keeping the peace between wars (Zetzel, 1997) and imposing rules on the people to promote agriculture (Johnston, 1980).
Keywords: Golden Age; Aeneid; Saturn; August; Rules